PENGARUH PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT DIIRINGI PEMBERIAN REWARD TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 25 PADANG - Gusmawidia, Susi; Delsi K, Delsi K (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research background is the students Comprehension of the concepts described by teachers remains low. Learning groups are conducted by teachers has never been in the form of team competition or race group. This study aims to determine whether students understanding of mathematical concepts by applying active learning model Learning Tournament type accompanied by the provision of rewards VIII.1 grade students better than students understanding of mathematical concepts with conventional learning graders VIII.2 SMPN 25 Padang. This type of research is experimental research, the research design Pre Experimental Design: static group comparison. The sampling technique was done by purposive sampling or sample aims. The research instrument is the ultimate test in the form of essays with the reliability of the test is 0,88. Based on the results of hypothesis testing usingÂ t test with Minitab Software obtained t > tÎ± is 1,83>1,645. This means that the hypothesis in this research received.